Tarekat sebagai Institusi Pendidikan Spiritual (Studi Fenomenologis Tarekat Syattariyyah Ponorogo) - Wahyudi Setiawan (Proceedings of Annual Conference for Muslim Scholars, 2017)
Tarekat is a spiritual institution that was built as the dakwah of Islam. Inside there are various methods and spiritual education that can deliver human being a good personality. This study aims to determine the model of spiritual education that is applied institutes to educate someone to be a perfect man. With descriptive phenomenological approach of this research is expected to be able to present the authentic objective field data.The results of this research that found spiritual education model implemented by the Tarekat Syattariyyah Ponorogo in educating the pilgrims. Begin from spiritual cleansing before the baiat procession, and then baiat, until mujahadah routinely performed alone or in the Mursyid’s home together. Use the model of spiritual education that is applied by the tarekat, each pilgrim can become qualified person physically and spiritually in this modern era.Keyword: Tarekat, Institution,Spiritual Education